Transmisi Emas Riwayat Kafil al-Yatim: Kajian Konstruksi Sanad dan Kedhabitan Perawi Hadits Nomor 6005 - Maulidaturrohmah Maulidaturrohmah (Salam Institute Islamic Studies, 2026)
This study examines the quality of the sanad of Sahih Bukhari Hadith No. 6005 regarding the virtue of providing for orphans through the takhrij and mustholah approaches. The method used is library research with descriptive qualitative analysis of the sanad and matan of the hadith, sourced from primary hadith books such as Sahih Bukhari, Sahih Muslim, Musnad Ahmad, Sunan Ibn Majah, and Muwatha'. The results of the study indicate that the main hadith is sahih with a muttashil chain of narration through tsiqah and dhabit narrators, from the Prophet Muhammad to Imam Bukhari through Sahl bin Sa'd, Abu Hazim, Abdul Aziz bin Abi Hazim, and Abdullah bin Abdul Wahhab. The study also identified 4 muttabi'ah hadiths and 6 syawahid hadiths that strengthen the quality of the main hadith with varying levels of quality from sahih, hasan, to da'if. The content of the hadith confirms that those who care for orphans (kafil al-yatim) will attain a noble position in Paradise alongside the Prophet Muhammad (peace be upon him).